Studi Kepustakaan Mengatasi Kesulitan Siswa dalam Memahami Konsep Matematika dengan Menggunakan Canva Ai Sebagai Media Visual & Audiovisual - Abd. Hamid Lindayo; Sudin Ninda; Fihirruddin Ishak Abd Jabar; Supardi Raun; Aryanti Pauh; Lia Nuhayati (Journal of Innovative and Creativity, 2025)
This study aims to analyze the use of Canva AI as a visual and audiovisual medium to address students' difficulties in understanding mathematical concepts. This literature review uses a qualitative approach through content analysis of scientific literature related to learning technology, visual media, and the use of AI in mathematics learning. The results of the study indicate that Canva AI can help students understand abstract concepts through visualizations, animations, and learning videos. Canva AI is effective in improving students' conceptual understanding, learning motivation, and representational thinking skills. However, challenges exist, including teachers' limited digital literacy, limited access to technology, and students' readiness to learn using digital media. This study concludes that Canva AI has the potential to improve the effectiveness of mathematics learning when integrated with appropriate pedagogical planning.